Assessment of the use of solar thermal collectors for desalination - Horta, Pedro (2015)
The use of renewable energy in desalination is the only sustainable way to decrease the water deficit without aggravating the energy crisis. Solar desalination is usually presented as the most optimal solution for sustainable desalination since the water needs are usually larger in places with high solar radiation. Considering the potential use of desalination as means of producing water in small isolated communities, the focus of this study lies on the use of solar energy in thermal desalination systems of small–medium capacity and low maintenance requirements. Based on typical values for the thermal energy requirements of such systems and on characteristic performance parameters of commercially available low-temperature solar thermal technologies, different system layouts are assessed and optimal system dimensioning is studied, for different locations, in terms of estimated water production costs.